2015
DOI: 10.5586/aa.2015.007
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effect of preparations of Betula pendula Roth., Chamomilla recutita L. and Urtica dioica L. on the initial growth of Hordeum vulgare L.

Abstract: The experiment investigated the effect of preparations of <em>Betula pendula</em>, <em>Chamomilla recutita</em>, and <em>Urtica dioica</em> on the initial growth of <em>Hordeum vulgare</em> under laboratory conditions. The experiment involved a water solution of sap from the trunk of <em>B. pendula</em>, an infusion from <em>Ch. recutita</em>, extracts from leaves and rhizomes as well as macerated herbage of <em>U. dioica</em>,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Several studies sought to demonstrate the allelopathic potential of nettle, which depends both on the concentration used and the plant species. For example, some studies showed the inhibitory effect of aqueous nettle extracts on barley [143], wind grass, and lambsquarters germination [144], whereas [145] showed that leaf and root extracts of Urtica dioica significantly reduced root mass. Khan et al [146] found a strong inhibitory effect of methanolic extracts of the stinging nettle on radish germination and growth.…”
Section: Nettle-associated Organismsmentioning
confidence: 99%
“…Several studies sought to demonstrate the allelopathic potential of nettle, which depends both on the concentration used and the plant species. For example, some studies showed the inhibitory effect of aqueous nettle extracts on barley [143], wind grass, and lambsquarters germination [144], whereas [145] showed that leaf and root extracts of Urtica dioica significantly reduced root mass. Khan et al [146] found a strong inhibitory effect of methanolic extracts of the stinging nettle on radish germination and growth.…”
Section: Nettle-associated Organismsmentioning
confidence: 99%
“…In this study, we tested four herbal species, known for their allelopathic effects: Hypericum perforatum [3], Urtica dioica [5,7,8], Achillea millefolium [9,10], and Matricaria chamomilla [4,11]. The Hypericum perforatum contains mainly hypericin (0.1%), but also triterpene saponins, tannins (8%), polyphenols, phenolic acids (chlorogenic, coffee, nicotine), phytosterols, essential oils, flavonoids (rutoside and quercitine; 4%) [12].…”
Section: Introductionmentioning
confidence: 99%